1994
DOI: 10.1007/bf01398733
|View full text |Cite
|
Sign up to set email alerts
|

Non-profit institutions in the United Nations System of National Accounts: country applications of SNA guidelines

Abstract: Based on a description of how non-profit institutions are defined in the System of National Accounts, this paper examines the actual treatment of non-profit institutions in several countries, and comes up with an overall assessment in terms of coverage and data quality. Finding both data coverage and quality poor across countries, we make two recommendations aimed at improving the presentation and understanding of non-profit institutions within the SNA. First, we suggest the introduction of a system by which n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…As a result, few countries have in the past collected systematic data on the nonpro¢t sector: among the some 170 countries employing the SNA, only France and Japan o¡er a full set of accounts, and some thirty others report partial information at best. And, as reported elsewhere (Anheier et al 1993, Anheier et al 1992, Salamon and Anheier 1996, published SNA data on the nonpro¢t sector preclude meaningful international and historical comparisons. Signi¢cant variations in measurement, coverage and data quality may either disguise true di¡erences or suggest false ones among the ¢gures reported.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…As a result, few countries have in the past collected systematic data on the nonpro¢t sector: among the some 170 countries employing the SNA, only France and Japan o¡er a full set of accounts, and some thirty others report partial information at best. And, as reported elsewhere (Anheier et al 1993, Anheier et al 1992, Salamon and Anheier 1996, published SNA data on the nonpro¢t sector preclude meaningful international and historical comparisons. Signi¢cant variations in measurement, coverage and data quality may either disguise true di¡erences or suggest false ones among the ¢gures reported.…”
Section: Introductionmentioning
confidence: 90%
“…A closer look at national accounts and input^output data, however, soon reveals that national and international data on the nonpro¢t sector are scant, incomplete and often of questionable quality (Salamon and Anheier 1996). In an earlier paper (Anheier, Rudney and Salamon 1993), we suggested that the inadequate data situation is primarily due to the way the nonpro¢t sector is treated in the UN System of National Accounts (SNA) and related systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation